Development Of Cognitive Mechanisms (In the Example of Future Geography Teachers) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article analyzes the development of cognitive mechanisms on the example of future geography teachers. In addition, this article discusses the role of pedagogical practice in training future teachers.